Efficacy and safety of ivonescimab in non-small cell lung cancer: a systematic review and meta-analysis of emerging clinical data - Dai, Youran; Xiao, Chenwei; Chen, Qi; Wang, Liang; Bo, Ruiqing; Cheng, Zerun; Pan, Guofeng (Frontiers in Pharmacology, 2026)
IntroductionIvonescimab (AK112), a novel bispecific antibody targeting PD-1 and VEGF, has emerged as a promising therapeutic agent in the treatment of non-small cell lung cancer (NSCLC). This study aims to comprehensively evaluate its efficacy and safety.Materials and methodsA comprehensive literature search was conducted in PubMed, Embase, Web of Science, and the Cochrane Library (from inception to January 2026) to identify studies reporting the clinical efficacy and safety outcomes of AK112 in NSCLC. Pooled analyses were conducted for efficacy endpoints, including objective response rate (ORR), disease control rate (DCR), and progression-free survival (PFS), as well as adverse events (AEs). For randomized controlled trials (RCTs), odds ratios (ORs) and hazard ratios (HRs) with 95% confidence intervals (CI) were calculated for binary and time-to-event outcomes, respectively. Subgroup analyses were performed by cancer type and treatment regimen.Results5 studies comprising 1,365 patients were included. AK112-based regimens significantly improved ORR (OR = 1.65, 95% CI: 1.31–2.09) and DCR (OR = 2.29, 95% CI: 1.18–4.44) compared to control treatments. A significant progression in PFS was observed (HR = 0.53, 95% CI: 0.45–0.62). The PFS benefit was consistent across all PD-L1 expression subgroups. Safety analysis revealed that AK112-based regimens increased the risk of all-grade AEs (OR = 2.05, 95% CI: 1.20–3.51) and grade ≥3 AEs (OR = 1.51, 95% CI: 1.19–1.92).ConclusionAK112 demonstrates significant efficacy and a manageable safety profile in advanced NSCLC, supporting its role as a valuable treatment option. Further studies are needed to confirm long-term survival benefits.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420251176434.